Conservation of Rafflesia hasseltii Suringar in Bukit Tiga Puluh National Park, Riau-Jambi - Ervizal A.M Zuhud; Nina Hernindiah; Agus Hikmat (Media Konservasi, 1999)
Ru/flesrcr ltasselfrr Suringar was fourid at Bukit Tiga Pululi National Park. Local name of this species is "cendawan muka harimua" Habitat o f R hasseltrr is lowland rain forest. As a holoparasite, R, hasseltii has no steam or leaves. The host of R, hasseltir is liana, such as Etrastigrna lanceolariuriz. Environmental factors, including biotic and abiotic factors, that affect the existence o f R. liasseltii are vegetation, animals, soil. climate and human activities.Conservation problems o f R. llasseltir are shifting cultivation, illegal cutting and other hurnan activities.